Regional Policy Coherence for the Great Green Wall Initiative: Unlocking Synergies Between the African Union’s Strategies on the Great Green Wall Initiative and Climate Change and Resilient Development for Stronger Climate Action - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This policy brief explores how strategic alignment between the African Union Great Green Wall Initiative Strategy and Ten-Year Implementation Framework (GGWI Strategy) (2024–2034) and the African Union Climate Change and Resilient Development Strategy and Action Plan (CCRDS) (2022–2032) can drive sustainable, climate-resilient development across Africa. It underscores the importance of policy coherence in addressing the interconnected challenges of land degradation, climate change, food insecurity, and poverty in Africa’s drylands. The brief identifies key areas of synergy, including landscape restoration, climate-smart food production, renewable energy deployment, sustainable livelihoods, and the use of nature-based solutions for adaptation and mitigation. Through interventions such as reforestation, agroforestry, and soil restoration, the GGWI Strategy contributes to ecosystem resilience, biodiversity conservation, and carbon sequestration. The brief also highlights the GGWI Strategy’s focus on strengthening governance and political commitment, leveraging technology, fostering cross-sectoral collaboration, and mobilising public and private investment. It promotes the integration of climate modelling and foresight tools for adaptive planning, the use of digital finance to support local communities, and the recognition of Indigenous knowledge in climate resilience strategies. Furthermore, the GGWI’s emphasis on addressing climate-induced migration and resource conflict through land restoration reinforces the critical link between environmental health and human security. Aligning the GGWI Strategy with the CCRDS will enhance implementation effectiveness, optimise resource use, and scale up Africa’s contributions to global climate and development goals, including those under the United Nations Framework Convention on Climate Change (UNFCCC) and the United Nations Convention to Combat Desertification (UNCCD).